Hyponatremia in children with lower respiratory tract infection: a cross-sectional study - Thani, Kamal Prasad; Shrestha, Sandeep; Gautam, Uttara; Keshari, Munna (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Lower respiratory tract infections (LRTIs) are leading cause of pediatric mortality in Nepal. Hyponatremia is common electrolyte imbalance in severe infections, but its prevalence and impact in high-altitude, resource-limited settings like Jumla are poorly characterized. This study aimed to determine prevalence and clinical significance of hyponatremia in children hospitalized with LRTIs. Methods: Hospital-based cross-sectional study was conducted from January 2024 to June 2025, including 80 children aged 1 month to 12 years with LRTIs. Serum sodium levels were measured, and hyponatremia was classified as mild (130-134 mEq/L), moderate (125-129 mEq/L), or severe (<125 mEq/L). Associations with clinical parameters and outcomes were analyzed. Results: Prevalence of hyponatremia was 56.3%, predominantly mild (77.8% of hyponatremic cases). Hyponatremia was significantly associated with clinical signs of severe respiratory distress, including chest indrawing (p=0.001), crackles (p<0.001), and nasal flaring (p=0.004). Children with hyponatremia had markedly higher needs for continuous positive airway pressure (CPAP) (48.9% vs. 2.9%, p<0.001) and ventilator support (22.2% vs. 5.7%, p=0.010). A longer hospital stay was strongly correlated with lower sodium levels (r = -0.43, p < 0.001). Furthermore, significant negative correlations were observed between serum sodium and both absolute neutrophil count (r = -0.57, p < 0.001) and white blood cell count (r = -0.42, p = 0.0001). Conclusion: Hyponatremia is highly prevalent among children with LRTIs in Jumla and is associated with increased disease severity, including respiratory support needs and prolonged hospitalization. Routine sodium screening can aid in risk stratification and guide fluid management in this vulnerable high-altitude population.